Opposing Effects on Vascular Smooth Muscle Cell Proliferation and Macrophage-induced Inflammation Reveal a Protective Role for the Proresolving Lipid Mediator Receptor ChemR23 in Intimal Hyperplasia - Artiach, Gonzalo; Carracedo, Miguel; Clària, Joan; Laguna-Fernandez, Andres; Bäck, Magnus (Frontiers in Pharmacology, 2018)
Intimal hyperplasia remains a significant clinical problem in for example coronary artery bypass graft failure. Since omega-3 fatty acids reduce intimal hyperplasia, we hypothesized that the G protein-coupled receptor ChemR23 for the omega-3-derived pro-resolving lipid mediator resolvin E1 drives those effects. ChemR23+/+ and ChemR23-/- mice were generated with or without introduction of the Caenorhabditis elegans fat-1 transgene, which leads to an endogenous omega-3 fatty acid synthesis and thus increasing the substrate for resolvin E1 formation. ChemR23 deletion significantly increased intimal hyperplasia 28 days after ligation of the left common carotid artery. Mice expressing the fat-1 transgene showed reduced intimal hyperplasia independently of ChemR23 expression. ChemR23-/- Vascular smooth muscle cells (VSMCs) exhibited a significantly lower proliferation compared with VSMCs derived from ChemR23+/+ mice. In contrast, ChemR23-/- peritoneal macrophages had significantly higher mRNA levels of pro-inflammatory cytokines compared with ChemR23+/+ macrophages. Finally, conditioned media transfer from ChemR23-/- macrophages to VSMCs significantly increased VSMC proliferation compared with conditioned media from ChemR23+/+ macrophages. Taken together, these results point to a dual effect of ChemR23 in resolution pharmacology by directly stimulating VSMC proliferation and at the same time suppressing macrophage-induced VSMC proliferation. In conclusion, these differential effects of ChemR23 signaling in VSMC and macrophages open up a novel notion for intimal hyperplasia pathophysiology, where ChemR23-transduced effects on the vascular wall may vary, and even be opposing, depending on the degrees of resolution of inflammation.